2017
DOI: 10.1371/journal.pone.0189992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tolerance to sunlight between spatially distant and genetically different strains of Lymantria dispar nucleopolyhedrovirus

Abstract: Baculoviruses are a family of insect-specific pathogenic viruses can persist outside for long periods through the formation of occlusion bodies. In spite of this ability, the UV of sunlight is an essential factor that limits the survival of baculoviruses outside the host. In the current study, we compared the UV tolerance of two strains of Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV), which were isolated in spatially different regions (LdMNPV-27/0 in Western Siberia (Russia) and LdMNPV-45/0 in North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A study of baculovirus transmission in forest tent caterpillars ( Malacosoma disstria ) found depressed transmission rates on forest edges as opposed to the forest interior, which was attributed to sunlight inactivating virus on leaves at forest edges (Roland & Kaupp, 1995). A field study of two strains of gypsy moth NPV showed variable resistance of virus to ultraviolet, in which inactivation rate from ambient ultraviolet was greater in a more potent strain than a less potent one (Akhanaev et al, 2017). In another study of forest tent caterpillars using tree ring analyses, it was suggested periods of weaker ultraviolet radiation increased the effect of forest tent caterpillar outbreaks on tree growth (Haynes, Tardif, & Parry, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study of baculovirus transmission in forest tent caterpillars ( Malacosoma disstria ) found depressed transmission rates on forest edges as opposed to the forest interior, which was attributed to sunlight inactivating virus on leaves at forest edges (Roland & Kaupp, 1995). A field study of two strains of gypsy moth NPV showed variable resistance of virus to ultraviolet, in which inactivation rate from ambient ultraviolet was greater in a more potent strain than a less potent one (Akhanaev et al, 2017). In another study of forest tent caterpillars using tree ring analyses, it was suggested periods of weaker ultraviolet radiation increased the effect of forest tent caterpillar outbreaks on tree growth (Haynes, Tardif, & Parry, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Effect of exposure periods to UV on virus was studied previously. Akhanaev et al, [25] studied the open area sunlight exposed virus strains for 0.25, 0.5, 1, and 2 hours and later per orally inoculated host larvae with the same doses of virus (5x10 5 ) and with doses leading to same effect ((Lethal Dose killing 90% of the insect pest (LD90)). Also, they observed that strain LdM NPV-45/ O, which previously gave high virulence against L. dispar larvae, was more sensitive to UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To initiate infection, groups of 250 fourth instar larvae were allowed to eat leaf discs (dia = 8 mm) containing a dried drop of suspension of 4 × 10 4 OBs/disc for LdMNPV-45/0 and 2 × 10 5 OBs/disc for LdMNPV-27/0 as described in detail by Akhanaev et al, 2017 [ 39 ]. The doses used significantly differed for the low- and high-virulence strains.…”
Section: Methodsmentioning
confidence: 99%